2018
DOI: 10.1007/s00401-018-1892-1
|View full text |Cite
|
Sign up to set email alerts
|

Synapsin III deficiency hampers α-synuclein aggregation, striatal synaptic damage and nigral cell loss in an AAV-based mouse model of Parkinson’s disease

Abstract: Parkinson's disease (PD), the most common neurodegenerative movement disorder, is characterized by the progressive loss of nigral dopamine neurons. The deposition of fibrillary aggregated α-synuclein in Lewy bodies (LB), that is considered to play a causative role in the disease, constitutes another key neuropathological hallmark of PD. We have recently described that synapsin III (Syn III), a synaptic phosphoprotein that regulates dopamine release in cooperation with α-synuclein, is present in the α-synuclein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 57 publications
6
61
2
Order By: Relevance
“…[6] Moreover, we showed that Syn III is another key component of aSyn insoluble fibrils extracted from the post-mortem brains of sporadic PD patients [7] and that Syn III is a crucial mediator of aSyn aggregation and toxicity. [8] Strikingly, our most recent findings suggest that threo-methylphenidate (MPH), a monoamine re-uptake inhibitor clinically approved for the treatment of attention deficits and hyperactivity disorder (ADHD) [9] and for ameliorating gait freezing in advanced PD, [10][11][12][13][14] is able to stimulate an aSyn/Syn III-mediated locomotor response, specifically in aSyn transgenic mice at a pathological stage that exhibit severe dopaminergic functional deficits. [15] This MPH action is lost upon in vivo Syn III gene silencing, [15] thus suggesting that this protein may act as a target for MPH.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Moreover, we showed that Syn III is another key component of aSyn insoluble fibrils extracted from the post-mortem brains of sporadic PD patients [7] and that Syn III is a crucial mediator of aSyn aggregation and toxicity. [8] Strikingly, our most recent findings suggest that threo-methylphenidate (MPH), a monoamine re-uptake inhibitor clinically approved for the treatment of attention deficits and hyperactivity disorder (ADHD) [9] and for ameliorating gait freezing in advanced PD, [10][11][12][13][14] is able to stimulate an aSyn/Syn III-mediated locomotor response, specifically in aSyn transgenic mice at a pathological stage that exhibit severe dopaminergic functional deficits. [15] This MPH action is lost upon in vivo Syn III gene silencing, [15] thus suggesting that this protein may act as a target for MPH.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of pathophysiology and implications, the results obtained in the longitudinal section indicates that at early stages in PD, the serotonergic system seems to be affected showing a disconnection of Raphe nuclei from projecting regions in the graph analyses. Axonal degenerations and loss of synaptic proteins and efficiency might account for the "disconnection" detected in this study at all 3 levels (brainstem/subcortical/cortical regions) [48,49].…”
Section: Discussionmentioning
confidence: 73%
“…In PINK1 knock out mice, overexpression of a-Syn in the substantia nigra resulted in enhanced dopaminergic degeneration as well as high levels of phosphorylated a-Syn, suggesting that the loss of PINK1 leads to an increased sensitivity to a-Syn-induced neuropathology (Oliveras-Salvá et al, 2014). The injection of rAAV-mediating human a-Syn overexpression in knock out mice for synapsin III (Syn III) shows that silencing of Syn III could prevent the a-Syn aggregation (Faustini et al, 2018). Moreover, the genetic background of animals is important in response to a-Syn overexpression.…”
Section: Overexpression Of A-syn Mediated By Raavmentioning
confidence: 99%